2008
DOI: 10.1007/s00285-008-0206-y
|View full text |Cite
|
Sign up to set email alerts
|

Backward bifurcation, equilibrium and stability phenomena in a three-stage extended BRSV epidemic model

Abstract: In this paper we consider the phenomenon of backward bifurcation in epidemic modelling illustrated by an extended model for Bovine Respiratory Syncytial Virus (BRSV) amongst cattle. In its simplest form, backward bifurcation in epidemic models usually implies the existence of two subcritical endemic equilibria for R(0) < 1, where R(0) is the basic reproductive number, and a unique supercritical endemic equilibrium for R(0) > 1. In our three-stage extended model we find that more complex bifurcation diagrams ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…This could be interpreted as saying that a particular endemic equilibrium was LAS if, and only if, the gradient of the bifurcation at that point was positive. Interestingly enough, Greenhalgh and Griffiths (2009) found that these straightforward stability patterns did not always occur when the BRSV model was extended to three stages. The vertical turning points of the more complicated bifurcation curves were not necessarily the points at which a change in the stability of the endemic equilibria occurred.…”
Section: Locally Asymptotically Stable Endemic Equilibria and The Bifmentioning
confidence: 92%
See 3 more Smart Citations
“…This could be interpreted as saying that a particular endemic equilibrium was LAS if, and only if, the gradient of the bifurcation at that point was positive. Interestingly enough, Greenhalgh and Griffiths (2009) found that these straightforward stability patterns did not always occur when the BRSV model was extended to three stages. The vertical turning points of the more complicated bifurcation curves were not necessarily the points at which a change in the stability of the endemic equilibria occurred.…”
Section: Locally Asymptotically Stable Endemic Equilibria and The Bifmentioning
confidence: 92%
“…We now investigate the possibility that more complicated bifurcation diagrams, of the type observed for the three-stage BRSV model by Greenhalgh and Griffiths (2009) The type of bifurcation curve as given in Figure 5. β .…”
Section: Bifurcation Diagrams For the Extended Cg Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the reason for the Hopf-bifurcation occurring at δ = δ H is mentioned here as backward bifurcation. We like to mention here that the notion of 'backward bifurcation' used here is completely different compared to the same phrase used in literature for epidemic models [19]. Fig.…”
Section: Backward Hopf-bifurcationmentioning
confidence: 99%